Thyroid hormone responses to acute aerobic exercise - Mustafa Ş. Akgül; Bilgehan Baydil (Physical Education of Students)
Background and Study Aim. Thyroid hormone responses to acute maximal aerobic exercise is still unclear, so the aim of the study is to investigate the effect of acute maximal aerobic exercise resulting in fatigue on blood thyroid levels in men and women.